2010
DOI: 10.1007/s11306-010-0215-x
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine profiling of plasma: discrimination of isomers and discovery of lung cancer biomarkers

Abstract: Lysophosphatidylcholines (lysoPCs) are a class of compounds that have a constant polar head, and fatty acyls of different chain lengths, position, degrees of saturation, and double bond location in human plasma. LysoPCs levels can be a clinical diagnostic indicator that reveals pathophysiological changes. In this work, a method was developed to discriminate between different types of lysoPCs using reversed phase ultra-performance liquid chromatography coupled to quadrupole time-of-flight mass spectrometry, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
71
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 50 publications
12
71
0
2
Order By: Relevance
“…UPLC-based metabonomics was used to find potential biomarkers by [53,54]. Decreased LPCs may be explained by Lands' cycle pathway.…”
Section: Lung Cancermentioning
confidence: 99%
“…UPLC-based metabonomics was used to find potential biomarkers by [53,54]. Decreased LPCs may be explained by Lands' cycle pathway.…”
Section: Lung Cancermentioning
confidence: 99%
“…27 In another MS study of specific compounds, namely, lysophosphatidylcholines (lysoPC), abnormal levels of lysoPC isomers with different fatty acyl positions were found in the plasma of lung cancer patients compared to controls. 28 Using a more global profiling approach, Jordan and colleagues reported the NMR analysis of paired tissue and serum samples from 14 subjects with two different lung cancer histological types (adenocarcinoma and squamous cell This exploratory study, although involving a limited number of samples, showed the potential of serum NMR metabonomics to differentiate between the two lung cancer types, as well as between cancer patients and controls. In addition to cancer, plasma metabolic profiling has also been applied to investigate other lung disorders, namely, severe childhood pneumonia 30 and sepsis-induced acute lung injury (ALI), 31 providing indication that distinct systemic metabolic signatures seem to be associated with different pulmonary pathologies.…”
mentioning
confidence: 99%
“…Owing to the lack of corresponding standard samples, all markers, except lysoPC(18:4), were identified solely according to the fragment ion on MS E and criteria of Jia et al (2008) and Liebisch et al (2002). Earlier literature (Bell-Parikh et al, 2003;Dong et al, 2010;Murphy et al, 2005) was further used to confirm the results. UHPLC-MS data from five normal rats and five dysmenorrhea syndrome rats after the administration of XFSWD at 30 min, 2 h, 6 h and 12 h revealed 376 peaks of negative ions and 122 peaks of positive ions, which were detected and processed via MarkerLynx using the same acquisition method and data fed to SIMCA-P for PLS, respectively.…”
Section: Analysis Of Metabolic Patterns In Rat Plasma With Uhplc-q-tomentioning
confidence: 99%